Improved FGF21 Sensitivity and Restored FGF21 Signaling Pathway in High-Fat Diet/Streptozotocin-Induced Diabetic Rats After Duodenal-Jejunal Bypass and Sleeve Gastrectomy - Liu, Qiaoran; Wang, Shuo; Wei, Meng; Huang, Xin; Cheng, Yugang; Shao, Yi; Xia, Pingtian; Zhong, Mingwei; Liu, Shaozhuang; Zhang, Guangyong; Hu, Sanyuan (Frontiers in Endocrinology, 2019)
Objective: Bariatric surgery can profoundly improve glucose and lipid metabolism in diabetic rats. Fibroblast growth factor 21 (FGF21) is an important hormone with multiple metabolic beneficial effects. Alterations in serum FGF21 levels after bariatric surgery have been reported with conflicted results. Here, we investigated the effect of bariatric surgeries on FGF21 expression and sensitivity. Methods: We performed duodenal-jejunal bypass (DJB), sleeve gastrectomy (SG) and sham surgery in diabetic rats induced by high fat diet and streptozotocin. Metabolic parameters, including body weight, food intake, glucose tolerance, and lipid profiles, were monitored. FGF21 levels in both serum and liver were measured after surgery. FGF21 signaling pathway including FGF receptor 1 (FGFR1), β-klotho (KLB) and phosphorylated extracellular signal-regulated kinase 1/2 (ERK1/2) was detected in the liver and white adipose tissue (WAT). We also determined FGF21 sensitivity postoperatively by acute recombinant human FGF21 injection. Oral glucose tolerance test (OGTT) and insulin tolerance test (ITT) were conducted immediately after FGF21 injection. Serum triglyceride (TG) and non-esterified fatty acid (NEFA) were measured and the mRNA levels of early growth response 1 (Egr1) and cFos in the liver and WAT were detected after FGF21 injection. Results: Improvements in glucose tolerance, insulin sensitivity, and lipid profiles were observed after bariatric surgeries along with ameliorated lipid metabolism in the liver and WAT. Serum and hepatic FGF21 levels decreased in both DJB and SG groups.FGFR1 and phosphorylated ERK1/2 levels increased in both DJB and SG groups 8 weeks after surgery. The expression of KLB was downregulated only in the WAT after DJB and SG. Significant alteration of OGTT and ITT were observed after acute FGF21 administration in DJB and SG groups. Serum TG and NEFA in DJB and SG groups also decreased after FGF21 administration. And increased mRNA levels of Egr1 and cFos were detected in the liver and WAT after DJB and SG surgeries. Conclusions: DJB and SG surgeries can downregulate hepatic expression of FGF21, restore FGF21 signaling pathway and improve FGF21 sensitivity.